Combining Techniques to Treat Isolated Deep Recession-Type Defects: A Case Report with Long-Term Stability - João Carnio; Anna Tereza Carnio (Case Reports in Dentistry)
Introduction. The purpose of this case report was to show the clinical long-term stability of a successful two-step root coverage procedure. A combination of two single techniques was used to treat an isolated deep-wide defect. Case Presentation. A 28-year-old female patient was referred in order to treat a single recession defect at #22. Due to her fear of dental procedures and a poor economic situation, the team developed an alternative solution. They used a modified apically repositioned flap (MARF) to increase the donor area and then a laterally positioned flap (LPF) to treat the root defect. Clinical evaluation at the three-year follow-up revealed complete resolution of the defect, a gain in clinical attachment, excellent esthetic results, and minor morbidity to the patient. Conclusion. The combination of the MARF and the LPF procedures was able to successfully treat a single deep recession defect with some advantages over traditional techniques such as simplicity, ideal color match of tissues, and the absence of palatal donor tissue.